A new method to determine electric vehicle range in real driving conditions. Issue 1 (16th December 2022) - Armenta-Déu, Carlos; Cattin, Erwan
The main goal of this paper is the development of a method that allows a control system to determine the electric vehicle (EV) driving range within the highest precision. The methodology has been developed for real driving conditions taking into account not only the kind of driving but also the road characteristics and the driving operational mode. Battery capacity change with discharge has been considered for the available energy. A simulation process has been developed to reproduce the driving characteristics of a daily trip considering the dynamic conditions and vehicle characteristics such as size, shape and mass. Five different driving modes are included in the study, acceleration, deceleration, constant speed, ascent and descent. Specific software has been developed to predict electric vehicle range under real driving conditions as a function of the characteristic parameters of a daily trip.